Homotopy Analysis Method and Homotopy Padé Approximants for Solving the Fornberg-Whitham Equation - Marasi, H.R.; Pourmostafa Aqdam, A. (Eurasian Mathematical Journal, 2015)
In this paper, the homotopy analysis method (HAM) is sharpened to solve the Fornberg-Whitham equation. Homotopy-Padé technique, and the use of proper initial gauss and auxiliary linear operator are employed to accelerate the convergence of approximations. Results demonstrate the power of the HAM equipped with these techniques in increasing the convergence rate and enlarging the region of convergence.